Reframing the evidence base for policy‐relevance to increase impact: a case study on forest fragmentation in the oil palm sector - Lucey, JM; Palmer, G; Yeong, KL; Edwards, DP; Senior, MJM; Scriven, SA; Reynolds, G; Hill, JK (Wiley, 2017)
1. It is necessary to improve knowledge exchange between scientists and decision‐makers so that scientific evidence can be readily accessed to inform policy. 2. To maximise impact of scientific evidence in policy development, the scientific community should engage more fully with decision‐makers, building long‐term working relationships in order to identify and respond to ‘policy windows’ with science that is reframed for policy‐relevance. 3. We illustrate the process and challenges using a case study in which we synthesised evidence from studies of habitat fragmentation to provide information for improved biodiversity conservation in the oil palm sector, resulting in the uptake of this research into new industry guidelines. 4. Policy implications. The case study demonstrates how having an in‐depth understanding of the ‘policy arena’ (the state of policy and the actors and influencing factors that affect policy) and responding with relevant and specific information, enabled effective uptake of science to inform the design of conservation set‐asides in the oil palm industry.